Resilience of Coastal Lake Barriers in Poland in Light of Geological and Bathymetric Data and Hydrodynamic Simulations - Różyński, Grzegorz; Cerkowniak, Grzegorz R. (Frontiers in Marine Science, 2022)
The paper presents a study on the insufficient resilience of three coastal lake barriers at the central part of the Polish Baltic Sea coast. Environmental qualities of those lakes belonging to the NATURA2000 network dictate efforts aimed at their conservation through the maintenance of the barriers. The use of recently elaborated high resolution geological surveys demonstrated previously underestimated severe sand scarcity and indicated high threats of enhanced erosion, breaching and overtopping of the barriers. Next, the investigation of alongshore variation of nearshore wave energy dissipation, basing on the available bathymetric records and the concept of ordinary and empirical equilibrium profiles, identified potential erosion hot spots along the barriers. Finally, the XBeach model was applied to simulate the effects of rare, heavy storms with the recurrence period of 20 years with and without climate change induced sea level rise. Overall, the results demonstrated high susceptibility of the barriers to frequent fragmentation and allowed for recommendations of protection measures minimizing interference into the natural landscapes. The novelty of the paper consists in the assessment of aftermaths of extreme events by combining recent advances in coastal geology and climate change effects.